Vulnerable Community in Earthquake Disaster Reconstruction Process in Sindhupalchok - Giri, Madhu (Shahid Kirti Multidisciplinary Journal, 2023)
Reconstruction and resilience programs led by the National Reconstruction Authority (NRA) have not specifically addressed the Dalit community’s issues of vulnerability and cultural heterogeneity. The NRA formed and implemented different policies and guidelines for all victims irrespective of their caste/ethnic, cultural, economic, and political status. Monolithic reconstruction and resilience policy failed to address the vulnerability and socio-cultural resilience of the Dalits. The state social engineering failed because the socio-cultural and political vulnerability of the Dalits was ignored both in policy and practice. The policy and practice of earthquake reconstruction replicated the traditional slogan of Nepali: ‘We all are Nepali and all Nepali are equal’. Moreover, it established a rule of thumb to address other disaster victims equally. What are Dalits’ knowledge and experiences of disaster reconstruction? What are the constraints and opportunities for the resilience of the Dalits? What are the resilience practices of the Dalits? Based on the field-based study, interviews, and observations, the paper explored the exclusion of Dalits participation both in policy formulation and implementation. The detailed fieldwork in 2018 explored the technological domination of the government and non-government agencies while implementing the resilience of Dalit community. The Dalits were at the bottom of the socio-cultural hierarchy, including power, prestige, and property. The major flaw of the reconstruction and resilience was ignorance of the diversity of victims and ignorance of people’s knowledge of cultural resilience. The policies did not support their marginality and vulnerability.